Study of hydration of sarcosine, formation of its zwitterion and their different oligomers in aqueous media: a Raman spectroscopic and theoretical study - Sharma, Poornima; Singh, Dheeraj K.; Gupta, Vineet; Asthana, B. P.; Mishra, P. C.; Singh, Ranjan K. (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
{Raman spectra of the biologically important molecule sarcosine (SAR) (C3H7NO2) were studied experimentally in aqueous solution at different concentrations. These spectra were also calculated theoretically using density functional theory (DFT) at the B3LYP/6-31 1++G(d,p) level. Further, all the observed normal modes were assigned through potential energy distribution (PED). Geometry optimization of SAR produced its three conformers with slightly different energies. The lowest energy conformer of SAR was selected for a systematic solvation study wherein different numbers of water molecules (nW
Keywords: DFT calculations; Hydration; Oligomer; Raman spectra; Sarcosine; Zwitterion